Quantitative prediction of overburden pressure and overpressure zones using well logs - a case study of an x-field in the Niger-delta basin, Nigeria - Opara, Chidozie; Ohakwereze, Michael; Adizua, Okechukwu (International Journal of Advanced Geosciences, 2018)
Prediction and evaluation of overburden pressure are critical for the exploration and production of hydrocarbon reservoirs. Overburden pressure was estimated using well log (density and sonic) data obtained from two wells (B1 and B2) of an X - Field within the Niger Delta basin. Overburden pressure depends primarily on the bulk density data. Bulk density was extracted from density and sonic logs based on the log signatures. The bulk density was then used to determine overburden pressure using Eaton’s equation. The results reveal that overburden pressure increases linearly with depth, and an overburden gradient of 1.0 psi/Ft. was obtained. The overburden pressure was used to estimate pore pressure and vertical effective stress and thus enabled the determination of overpressure zones within the well.